PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 54 SEBANGAR KECAMATAN MANDAU KABUPATEN BENGKALIS - Sumirah '; Mahmud Alpusari; zairul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted because of the result of learning IPA class IVA SD Negeri 54 Sebangar. From 25 student who achieve KKM just 10 student (38,46%) while student who did’nt complete 15 student (61,54 %) with an average of 60. The purpose of this research to improve learning outcomes IPA Class IVA SD Negeri 54 Sebangar with application of learning models talk think write. The results obtanined by the average value of 69 basic score increased by 83,2% to 2080. In the second cycle the average value of student also increased by 86,8% to 2170. On the basic of completeness score IPA student learning outcomes is only 52 % ( not finished ). After the professor of applied learning model Numbered Head Together ( NHT ) in the first cycle classical completeness increased to 96 %, the second cycle of classical completeness obtained are increased to increase to 96 %. Activities of teacher at the first meeting of 54,54 % with enough categories. The second meeting increased to 72,72 % in both categories. In the second cycle increased to 79,54 % with the categories both. At a meeting of the second meeting of the second cycle, the activity of teacher increased to 81,81 % with the category very well. Activities of student in the first cycle of the meeting activity student acquire a percentage of 52,27 % in enough categories. The second meeting of the first cycle to 68,18 % in both categories. At the first meeting of the second cycle of student activity increased to 70,45 % with the categories both, and at the second meeting of the second cycle increased again to 79,54 % with categories both. Key Words : Numbered Head Together, learning outcomes IPA